PENGARUH CURRENT RATIO, DEBT TO ASSET RATIO, DAN PERPUTARAN MODAL KERJA TERHADAP RETURN ON ASSET PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KOMSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 – 2017 - Felicia Felicia; Dui Ariyanti; Titi Titi; Velycia Velycia; Ronald Hasudungan Rajagukguk (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
This study aims to prove and analyze the effect of Current Ratio, Debt to Asset Ratio, Working Capital Turnover on Return on Assets in consumer goods industry sector companies listed on the Indonesia Stock Exchange in 2013-2017. The population in this study is 42 goods industry sector companies’ consumption listed on the Indonesia Stock Exchange in 2013-2017. Of 42 listed companies, 24 sample companies were selected using purposive sampling. The results of the discussion showed that simultaneously independent variables; Current Ratio, Debt to Asset Ratio, Working Capital Turnover with the F test, together affect the Return on Asset. Partial results with the T test, the variable Debt to Asset Ratio affects the Return on Asset, while the Current Ratio, Working Capital Turnover has no effect and is not significant on Return on Assets.